Implementation of Regional Asset Accounting Information System in the Manado City Government - Lolowang, Missi Injilia; Morasa, Jenny; Lambey, Robert (Journal of Finance and Business Digital, 2024)
The Regional Asset Accounting Information System is designed to manage and deliver all accounting information related to Regional Assets (BMD) by utilizing existing methodologies. The aim of this study is to assess the implementation of the Regional Asset Accounting Information System at the Financial and Asset Management Agency of Manado, North Sulawesi. This research was carried out at the Financial and Asset Management Agency of Manado, North Sulawesi, using a descriptive qualitative research method, which involves the description, illustration, analysis, and comparison of written and oral data. The study’s findings indicate that the Regional Asset Accounting Information System employed by the Financial and Asset Management Agency of Manado adheres to the relevant regulations.